2010
DOI: 10.1017/s1366728909990010
|View full text |Cite
|
Sign up to set email alerts
|

The impact of bilingualism on the executive control and orienting networks of attention

Abstract: The main objective of this article is to provide new evidence regarding the impact of bilingualism on the attentional system. We approach this goal by assessing the effects of bilingualism on the executive and orienting networks of attention. In Experiment 1, we compared young bilingual and monolingual adults in a numerical version of the Stroop task, which allowed the assessment of the executive control network. We observed more efficient performance in the former group, which showed both reduced Stroop Inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
175
10
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(201 citation statements)
references
References 43 publications
11
175
10
5
Order By: Relevance
“…Furthermore, group differences in the ANT were found in the orienting network, running counter to results obtained with adult bilinguals in Hernández, Costa, Fuentes, Vivas, and Sebastián-Gallés (2010). It is possible that whereas all children in the current study profited from the spatial cue indicating the correct location of the following target, the bilingual and trilingual children were able to exploit the orienting cue to a significantly greater extent than the second-language learners.…”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore, group differences in the ANT were found in the orienting network, running counter to results obtained with adult bilinguals in Hernández, Costa, Fuentes, Vivas, and Sebastián-Gallés (2010). It is possible that whereas all children in the current study profited from the spatial cue indicating the correct location of the following target, the bilingual and trilingual children were able to exploit the orienting cue to a significantly greater extent than the second-language learners.…”
Section: Discussioncontrasting
confidence: 99%
“…The relationship of an IOR paradigm to active inhibitory control processes, on the other hand, is a much more ambiguous case, given that opinions are highly divergent on the causes (Hunt & Kingstone, 2003;Klein, 2000;Souto & Kerzel, 2009) and effects (Abrams & Dobkin, 1994;Taylor & Klein, 2000) of IOR. Thus, it is difficult to discern what greater IOR for bilinguals as compared to monolinguals (Colzato et al, 2008; but see Hernández et al, 2010, for a nonreplication) might mean. On a historical note, the Colzato et al investigation, showing greater IOR in bilinguals at long cue-target intervals, concluded that this language group possesses a superior ability to maintain action goals, whereas a greater spatial negative-priming effect in bilinguals (Treccani et al, 2009) has been taken as evidence in favor of BICA.…”
Section: Overall (Global) Rt Effects: Overviewmentioning
confidence: 99%
“…What is the precise role of attentional control in SLA (Rai, Loschky, Harris, Peck, & Cook, 2011)? How does bilingualism impact WM (Hernández, Costa, Fuentes, & Vivas, 2010)? And what cognitive training practices increase WM and facilitate L2 learning (Klingberg, 2010)?…”
Section: Resultsmentioning
confidence: 99%